Nationalism and Belonging in India, Pakistan and South Central Asia: Some Comparative Observations - Bedford, Ian (The Australian journal of anthropology, 1996)
The criteria invoked in the definition of national identity are commonly derived from contexts other than those of the nation-state itself—most notably those of territoriality, language/culture, kinship/descent and religion. It therefore follows that in seeking to understand the kind of identity or belongingness invoked in a particular instance of national ideology it is necessary to explore not only the kind of nation-state envisaged, but also those non-national forms of belonging or community from which the national ideology may itself be historically derived. In this paper I seek to develop this argument by comparing some of the principal forms of nationalism found in India, Pakistan and Central Asia. I pay particular attention to the importance of the concept qawm, which in Pakistan, Afghanistan and elsewhere in Central Asia, is used to refer to a wide variety of groups to which people owe allegiance. Such usages alert us to the important fact that the nation, as ‘imagined community’, may have its origins as a political movement among sentiments and allegiances which draw on pre-modern social arrangements and are in tension with ‘nationalist’ exclusivism. Even when the nation (as nation-state) has been secured, so-called ‘nationalist’ revivalism, while taking the nation for granted, may in fact appeal to sentiments of a different kind.